Knowledge, attitude & practice on HIV/AIDS among the spouses of labor migrants to India, in daiji VDC pf kanchanpur district , Nepal. - Chataut, Ranjana (2011)
ABSTRACT: This research was conducted on the four VDCs in Daiji of Kanchanpur District of Far Western region. The purpose of this study was to find out the knowledge, attitude and practice of HIV/AIDS among the spouses of labor migrants to India. Discussing about the demographic characteristics, 51.2% had nuclear type of family and 44.4% had joint family. According to 2001 census report total house hold of Daiji VDC was 2088 . ALSO the total population of Kanchanpur district was 377,899 & Daiji was 6597 according to 2001 census & literacy rate was 57.60% (Male, 70.53%; Female, 44.19%) according to my study ,the literacy was 33.8 among women. And Majority of the respondents belong to Hindu religion i.e., 95.6%.Most of the respondent were illiterate & the type of family was mostly nuclear type of family which determines social behaviour of the respondents family. Along with the married the widows were also there whose husband died due to HIV/AIDS. And the working place of husband was mostly in Mumbai which is one of the large cities in India & carries a higher risk for HIV transmission & they mostly visit Nepal in every six months. And regarding the occupation of the respondents,(68.1%) were involved in agriculture from which there was no cash income just for feeding,14.4% income was from labor work,3.8% from business & others don't have any. Majority i.e. 98.1% percent haven't heard about HIV/AIDS and only 74.4% had known that it can be transmitted . most of respondents have a perception that HIV is fatal. Among the total respondents 48.8% of respondents known that HIV/AIDS can be prevented &46.2% didn't know about preventive measures. Among the total respondents 70.6%% said HIV/AIDS can be cured & similarly more than half 63.1 % replied that they are at higher risk this implicts that they had good level of awareness.33.8% use any kind of protective measures which prevents them from future transmission of HIV/AIDS,58.8% didn't use any kind of protective measures & some respondents(7.5%) are still unaware about this. Most of the people if suffered they chose to go VCT centre but consulting doctors or health post before. Nearly half of the respondent (41.8%) have tested for HIV/AIDS & some of them HIV/AIDS but have good practice of doing treatment. The services declared by the government of Nepal were no available in the district &different problems arising during providing service. Where these condition promoting the risk behaviour other than controlling risk activities by the awareness programme.